2013
DOI: 10.1007/s13277-013-0824-x
|View full text |Cite
|
Sign up to set email alerts
|

PAK5-Egr1-MMP2 signaling controls the migration and invasion in breast cancer cell

Abstract: p21-activated kinases (PAKs) are activated by various extracellular stimuli and, in turn, activate other kinases by phosphorylating them at specific serine/threonine residues or through protein-protein interaction. As a recently identified member of the group B PAK family, the role of PAK5 in cancer is poorly understood. In this study, we investigated the effect of PAK5 on the malignant phenotype, such as proliferation, cell cycle, apoptosis, migration, and invasion. Cell growth assay and cell cycle analysis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…However, the overexpression of PAK7 increases the migration and invasion of colon cancer cells in vitro . Our findings are consistent with other recent studies, which have identified an important role of PAK7 in tumorigenesis and metastasis of breast, pancreatic, and gastric cancer cells [21, 27, 28]. …”
Section: Discussionsupporting
confidence: 94%
“…However, the overexpression of PAK7 increases the migration and invasion of colon cancer cells in vitro . Our findings are consistent with other recent studies, which have identified an important role of PAK7 in tumorigenesis and metastasis of breast, pancreatic, and gastric cancer cells [21, 27, 28]. …”
Section: Discussionsupporting
confidence: 94%
“…In the network presented herein, miR-9 directly targeted HMGA2, EGR1 and IGFBP3. These three coding RNAs are closely related to the invasion and metastasis of breast cancer [20, 26, 27]. The expression level of miR-210 in MDA-MB-231 cells is 4 times higher than that in MCF-7 cells in the present study.…”
Section: Discussionmentioning
confidence: 45%
“…Genetic experiments suggest that Pak mediates certain aspects of extracellular matrix organization downstream of CDC42, as matrix remodeling could not be restored to Cdc42 −/ − MEFs by reintroducing mutants of CDC42 that lacked Pak binding 60 . PAK1, 2, 4, and 5 have been shown to regulate MMP expression in a variety of cancer cell types 61, 626364 . Increased expression of MMPs has been suggested to result from Pak-mediated activation of JUN N-terminal kinase (JNK) 65, 66 .…”
Section: Activating Invasion and Metastasismentioning
confidence: 99%